2007
DOI: 10.2118/88736-pa
|View full text |Cite
|
Sign up to set email alerts
|

Expandable Tubular Completions for Carbonate Reservoirs

Abstract: A major Middle East operator has applied expandable tubular solutions for water shutoff and zonal isolation in fractured carbonate reservoirs. In this paper, we review the operator's experience with the implementation of this emerging well technology. Expandable tubular solutions have proven successful in terms of installation reliability, isolation of fractures, and zonal isolation without cement to segment horizontal wells.Case histories highlight the benefits, risks, and performance of expandable tubular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Conserving hole size, or diametric efficiency (DE), allows additional pipe strings to be deployed to drill deeper or farther. Marketz et al [33] described the application of SET in carbonate reservoirs. The technology, when used on trial basis in more than 20 wells in fractured carbonate reservoirs, demonstrated success with expandable tubular solutions to replace scab liners for fracture shutoff and to replace cement for zonal isolation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conserving hole size, or diametric efficiency (DE), allows additional pipe strings to be deployed to drill deeper or farther. Marketz et al [33] described the application of SET in carbonate reservoirs. The technology, when used on trial basis in more than 20 wells in fractured carbonate reservoirs, demonstrated success with expandable tubular solutions to replace scab liners for fracture shutoff and to replace cement for zonal isolation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Up till now some 51 horizontal producers and 26 horizontal injectors have been drilled of which 17 are multi laterals. In the drilling phase the fractures, which are inferred by severe losses or identified by Formation Micro Imager logging (FMI), have been shut off initially by scab liners (4 ½ pipe with External Casing Packers) and later by expandable 5 ½" liners [4]. Despite these precautions some 27 barefoot horizontal wells produce with water cuts above 50 % or are closed due to very high water cuts.…”
Section: Introductionmentioning
confidence: 99%